A review of Spathipheromyia (Diptera: Muscidae) from Argentina with the description of an extra-large new species - Patitucci, Luciano Damián; Olea, María Sofía; Mulieri, Pablo Ricardo (Zootaxa, 2019)
Spathipheromyia Bigot is a small group of predaceous muscids endemic of the Neotropical region. Currently, the genus includes 14 species of which only Spathipheromyia atra Malloch, 1934, S. magellani Malloch, 1934 and S. guttipennis (Thomson, 1869) are listed for Argentina. We present a new species Spathipheromyia goliat sp. nov. for Argentina and registered S. albiceps Malloch, 1934 for the first time for Argentina. Also we present a more detailed description of male and female terminalia of S. albiceps, S. atra, and S. guttipennis, notes on their habitat, new records, a key to species, and a discussion on structure of male terminalia.